The Development of the Turkish Craving for Online Shopping Scale: A Validation Study - Savci, Mustafa; Ugur, Erol; Ercengiz, Mustafa; Griffiths, Mark D. (Springer, 2023)
In the present study, the Turkish version of the Craving for Online Shopping Scale (TCOSS) was developed by modifying items on the Penn Alcohol Craving Scale (PACS). The sample comprised 475 adult volunteers (233 women and 242 men) from three different non-clinical samples recruited online. The structure validity of the TCOSS was examined utilizing exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and criterion validity testing. The EFA showed that the TCOSS had a unidimensional structure that explained 80% of the total variance. The five-item unidimensional structure of the TCOSS then underwent further testing using two different samples. First, the structure of the TCOSS was tested using CFA, which confirmed the unidimensional factor structure. Second, measurement invariance of the TCOSS was conducted through structural invariance, metric invariance, and scalar invariance across different samples. This demonstrated the TCOSS had measurement invariance across different samples (CFA and criterion validity samples). Criterion validity of the TCOSS was tested using the Internet Addiction Test-Short Form, Brief Self-Control Scale, Compulsive Online Shopping Scale, Positive and Negative Affect Schedule, and self-reported personal information. According to the criterion validity results, the TCOSS assessed the structure it targets. Cronbach's alpha internal consistency coefficients of the TCOSS were .94 in the EFA sample, .94 in the CFA sample, and .96 in the criterion validity sample. When validity and reliability analysis of the TCOSS are considered as a whole, it is concluded that the TCOSS is a valid and reliable scale for assessing craving for online shopping among online shoppers.
Keywords: Online shopping; Online shopping addiction; Craving; Online shopping craving